2013
DOI: 10.1038/mt.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus-mediated Expression of Human Erythropoietin in Tumors Enhances Virotherapy and Alleviates Cancer-related Anemia in Mice

Abstract: Recombinant human erythropoietin (rhEPO), a glycoprotein hormone regulating red blood cell (RBC) formation, is used for the treatment of cancer-related anemia. The effect of rhEPO on tumor growth, however, remains controversial. Here, we report the construction and characterization of the recombinant vaccinia virus (VACV) GLV-1h210, expressing hEPO. GLV-1h210 was shown to replicate in and kill A549 lung cancer cells in culture efficiently. In mice bearing A549 lung cancer xenografts, treatment with a single in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The majority of approaches to arming OVs can equally be applied in the treatment of any solid malignancy. Exceptions include recombinant human erythropoietin (rhEPO), which was recently engineered into an oncolytic Lister strain vaccinia virus (GLV-1h210) and tested in lung cancer xenografts (Nguyen et al, 2013). rhEPO is essential for erythropoiesis and significantly improves quality of life in anaemic cancer patients, but is associated with angiogenesis, limiting its use in highly vascularized tumours such as HCC (Yasuda et al, 2003;Crawford et al, 2002).…”
Section: Enhancing Anti-cancer Efficacymentioning
confidence: 99%
“…The majority of approaches to arming OVs can equally be applied in the treatment of any solid malignancy. Exceptions include recombinant human erythropoietin (rhEPO), which was recently engineered into an oncolytic Lister strain vaccinia virus (GLV-1h210) and tested in lung cancer xenografts (Nguyen et al, 2013). rhEPO is essential for erythropoiesis and significantly improves quality of life in anaemic cancer patients, but is associated with angiogenesis, limiting its use in highly vascularized tumours such as HCC (Yasuda et al, 2003;Crawford et al, 2002).…”
Section: Enhancing Anti-cancer Efficacymentioning
confidence: 99%
“…However, other animal studies showed no evidence of such deleterious effects (8385). A recombinant GLV-1h210 expressing hEPO was constructed, and the effects of intratumorally expressed hEPO on tumor growth were examined in xenografted mice bearing human lung cancer (86). Insertion of the hEPO gene did not compromise virus replication (86).…”
Section: Vaccinia Virus Oncolytic Virotherapymentioning
confidence: 99%
“…A recombinant GLV-1h210 expressing hEPO was constructed, and the effects of intratumorally expressed hEPO on tumor growth were examined in xenografted mice bearing human lung cancer (86). Insertion of the hEPO gene did not compromise virus replication (86). Intravenous injection of GLV-1h210 resulted in tumor-specific production and secretion of functional hEPO, which significantly increased red blood cell numbers and hemoglobin levels (86).…”
Section: Vaccinia Virus Oncolytic Virotherapymentioning
confidence: 99%
See 2 more Smart Citations